2016
DOI: 10.5114/aoms.2015.55012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the quality of life of postmenopausal osteoporotic and osteopenic women with or without fractures

Abstract: IntroductionMost studies concerned with the quality of life (QoL) of women with reduced bone mineral density (BMD) focus on patients with vertebral and non-vertebral fractures. Our objective was to evaluate QoL among patients with reduced BMD regardless of their fracture history compared to women with normal BMD.Material and methodsEighty-five patients in the study group were classified as osteoporotic, with BMD results measured by densitometry and expressed by T-score ≤ –2.5 SD, 122 women were osteopenic, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 29 publications
6
22
1
3
Order By: Relevance
“…The problem of bone density tests in women is current and it is necessary to thoroughly understand the risk factors of osteopenia and osteoporosis. Interesting new directions of research include the assessment of the influence of alcohol, coffee, and tea on BMD [41], quality of life [42], as well as detailed studies of the relationship between BMD and other diseases [43] and with biomarkers in blood [44].…”
Section: Bmd -Bone Mineral Density Bmc -Bone Mass Dis -Distal Poinmentioning
confidence: 99%
“…The problem of bone density tests in women is current and it is necessary to thoroughly understand the risk factors of osteopenia and osteoporosis. Interesting new directions of research include the assessment of the influence of alcohol, coffee, and tea on BMD [41], quality of life [42], as well as detailed studies of the relationship between BMD and other diseases [43] and with biomarkers in blood [44].…”
Section: Bmd -Bone Mineral Density Bmc -Bone Mass Dis -Distal Poinmentioning
confidence: 99%
“…Therefore, studies have been developed that measure the quality of life of these patients, who are determined by their degree of functionality. This has been confirmed in women with osteopenia and osteoporosis; since they have limited physical activity, they have altered the physical position, suffering, and pain, with mental and emotional alterations [22].…”
Section: Diseases and Ethical Considerationsmentioning
confidence: 88%
“…This pathology results from the decrease in estrogen production, reduced calcium resorption, increased urinary excretion, reduced vitamin D synthesis, as well as less formation of its active metabolites, decrease in the number of vitamin D receptors. The analysis of the quality of life of women with osteopenia or osteoporosis is important, as it can guide pharmacological and non-pharmacological strategies [8].…”
Section: Hormonal Profile Signs and Symptomsmentioning
confidence: 99%
“…It is suggested that the quality of life assessed on the QUALEFFO 41 scale differs between continents and ethnic groups. In most analyses, QoL was lowest in Asia and Europe and highest in North America and Oceania [16].Further research is undoubtedly needed to understand this phenomenon.…”
Section: Discussionmentioning
confidence: 99%